Searching for the Divine: An Autoethnographic Account of Religious/Spiritual and Academic Influences on the Journey to Professor. - Baesler, E. James (Journal of Communication & Religion)
This autoethnographic account chronicles my academic and religious/spiritual path to becoming a professor of Communication. Spiritual influences and significant life events related to prayer, education, teaching, and research serve as sign posts marking the way. The journey begins with a child scientist experimenting with life--and an adolescent discovering the joy of reading through an illness. The journey continues with a crisis in undergraduate years followed by indoctrination stories of graduate school. Securing and retaining an academic position in Communication reveals the complexities of negotiating research and teaching in higher education. After tenure and promotion, a concurrent spiritual awakening begins a two decade "prayer research journey." Finally, the journey continues with the most recent transition, moving from a social science research orientation to a new methodological orientation toward scholarship called autoethnography. Questions for meditation and reflection periodically punctuate the journey as a way to engage with the reader and facilitate reflection for life praxis.